Changes in different body fluids during simple intestinal obstruction in buffaloes - Mohan, Raj; Saini, N S; Singh, S S (The Indian Journal of Animal Sciences, 2011)
In clinical cases of buffaloes suffering from simple intestinal obstruction (12) changes in blood, peritoneal and rumen fluids were investigated. Haematological parameters like PCV, Hb and TLC were within normal limits, whereas neutrophilic to lymphocytic cell ratio reversed. Blood biochemistry revealed no changes in plasma globulin, sodium and potassium levels but inorganic phosphorus, BUN, and creatinine were increased, whereas concentrations of total protein, albumin, calcium, and chloride were decreased. Alterations in majority ofthe biochemical parameters ofperitoneal fluid reflected a systemic change. Cytological examination ofperitoneal fluid showed no changes while rumen chloride was high. Â